Sigmar1 ablation leads to lung pathological changes associated with pulmonary fibrosis, inflammation, and altered surfactant proteins levels - Remex, Naznin Sultana; Abdullah, Chowdhury S.; Aishwarya, Richa; Nitu, Sadia S.; Traylor, James; Hartman, Brandon; King, Judy; Bhuiyan, Mohammad Alfrad Nobel; Kevil, Christopher G.; Orr, A. Wayne; Bhuiyan, Md. Shenuarin (Frontiers in Physiology, 2023)
Sigma1 receptor protein (Sigmar1) is a small, multifunctional molecular chaperone protein ubiquitously expressed in almost all body tissues. This protein has previously shown its cardioprotective roles in rodent models of cardiac hypertrophy, heart failure, and ischemia-reperfusion injury. Extensive literature also suggested its protective functions in several central nervous system disorders. Sigmar1’s molecular functions in the pulmonary system remained unknown. Therefore, we aimed to determine the expression of Sigmar1 in the lungs. We also examined whether Sigmar1 ablation results in histological, ultrastructural, and biochemical changes associated with lung pathology over aging in mice. In the current study, we first confirmed the presence of Sigmar1 protein in human and mouse lungs using immunohistochemistry and immunostaining. We used the Sigmar1 global knockout mouse (Sigmar1−/−) to determine the pathophysiological role of Sigmar1 in lungs over aging. The histological staining of lung sections showed altered alveolar structures, higher immune cells infiltration, and upregulation of inflammatory markers (such as pNFκB) in Sigmar1−/− mice compared to wildtype (Wt) littermate control mice (Wt). This indicates higher pulmonary inflammation resulting from Sigmar1 deficiency in mice, which was associated with increased pulmonary fibrosis. The protein levels of some fibrotic markers, fibronectin, and pSMAD2 Ser 245/250/255 and Ser 465/467, were also elevated in mice lungs in the absence of Sigmar1 compared to Wt. The ultrastructural analysis of lungs in Wt mice showed numerous multilamellar bodies of different sizes with densely packed lipid lamellae and mitochondria with a dark matrix and dense cristae. In contrast, the Sigmar1−/− mice lung tissues showed altered multilamellar body structures in alveolar epithelial type-II pneumocytes with partial loss of lipid lamellae structures in the lamellar bodies. This was further associated with higher protein levels of all four surfactant proteins, SFTP-A, SFTP-B, SFTP-C, and SFTP-D, in the Sigmar1−/− mice lungs. This is the first study showing Sigmar1’s expression pattern in human and mouse lungs and its association with lung pathophysiology. Our findings suggest that Sigmar1 deficiency leads to increased pulmonary inflammation, higher pulmonary fibrosis, alterations of the multilamellar body stuructures, and elevated levels of lung surfactant proteins.